Pembuatan Website UMKM Fairyani Cake Menggunakan Blogger Untuk Pengembangan Pemasaran Dan Promosi - Desy Rahmawati Ningsih; Muhammad Sadam; Dian Rahayu (CV. ITTC INDONESIA, 2024)
Fairyani cake is a business that sells textured cakes with a soft, sweet and savory taste. Made with love, this cake has a soft texture like a cloud with a layer of fine sugar that makes every bite feel like a sweet hug located at Jl. Air Gull, Parak Gadang, West Sumatra, Padang City. Cake is a soft dough consisting of flour, sugar, fat, eggs and other additional ingredients, because it has a soft, soft, not weak and not brittle texture. The author conducted interviews and documentation and created a website aimed at increasing the sales appeal of Faryani Cake. Apart from that, through the website the information that has been created is provided in detail, complete, and can provide a more attractive appearance. The method used in collecting data is a qualitative method by conducting interviews and documentation. The author visited and made direct observations at the Farayani Cake shop to obtain the necessary data related to the design. This design produces the main media in the form of Instagram information @Fairyani Cake